A cadeira que aprisiona e o cavalo que liberta: um estudo sobre Equoterapia e Bem-Estar Subjetivo em usuários de cadeira de rodas. - André Luiz de Melo (2021)
Widespread in Brazil and worldwide, equine-assisted therapy is a therapeutic and educational method that uses the horse in an interdisciplinary context that encompasses health, education and riding. Moreover, it contributes both to motor rehabilitation regarding the various demands of physical health, and to practitioners' mental health. Therefore this study aimed to analyze the association of equine assisted therapy with the subjective well-being of wheelchair users. Accordingly, a qualitative approach was adopted with a semistructured interview as a data collection tool. Altogether, there were 20 participants, 4 wheelchair users, 6 family members or significant others, 4 coordinators and 6 therapists, divided into 2 studies. Nvivo was used to analyze the obtained self-reports. Three other theoretical studies were also developed, a narrative review and two systematic reviews. The two original studies were supported by data triangulation that suggested an intimate relationship among the practitioner of equine-assisted therapy, the segments involved in the treatment and the equine-assisted therapy environment, which highlighted indicators of subjective well-being and relationships in the category of analysis. The first study showed a greater evidence in the subcategories affection, selfesteem and happiness, as well as overcoming fear in the category of analysis of coping strategies. The Second Study highlighted overcoming fear, happiness and self-esteem. The category of relationship evidenced the relationship with the horse, with the environment, with the family and with oneself. In this sense, the results have shown that the equine-assisted therapy practice might improve the levels of the practitioner's subjective well-being. It was concluded that equineassisted therapy can be positively associated with the subjective well-being of wheelchair users. However, as it became apparent in the systematic reviews, further investigations are needed to fill in the literature gaps and reinforce the thesis that equine-assisted therapy is associated with the subjective well-being of wheelchair users. KEYWORDS: EQUINE-ASSISTED THERAPY, SUBJECTIVE WELL-BEING, WHEELCHAIR USER